Government Spending on Agriculture and Economic Growth Nexus in Nepal: An ARDL Bounds Testing Approach - Adhikari, Reena; Adhikari, Gyan Mani; Dhungana, Agya (Dristikon: A Multidisciplinary Journal, 2026)
This study investigates the relationship between government spending on agriculture and economic growth in Nepal using the Autoregressive Distributed Lag (ARDL) bounds testing approach with annual data spanning from 1990 to 2023. As an agrarian economy where agriculture contributes approximately one-quarter of GDP and employs nearly two-thirds of the population, understanding the growth implications of agricultural public expenditure is critical for development policy formulation. Our empirical findings reveal several key insights: First, government spending on agriculture exhibits a positive and statistically significant long-run relationship with economic growth, with elasticity estimates suggesting that a ten percent increase in agricultural expenditure raises GDP growth by approximately one percentage point. Second, the relationship displays diminishing returns, indicating optimal expenditure thresholds beyond which additional spending generates progressively smaller growth dividends. Third, the composition of agricultural spending matters significantly, with expenditure on irrigation infrastructure and rural roads demonstrating substantially stronger growth impacts compared to agricultural subsidies. Fourth, cointegration analysis confirms stable long-run equilibrium relationships despite short-term fluctuations, with adjustment speeds indicating that deviations from equilibrium are corrected within two to three years. The study contributes to the development economics literature by providing robust empirical evidence on the agriculture-growth nexus in a least developed country context, with important implications for public expenditure prioritization, sectoral resource allocation, and rural development strategy.